Doctors' experience of coordination across care levels and associated factors. A cross-sectional study in public healthcare networks of six Latin American countries (2017)
Improving coordination between primary care (PC) and secondary care (SC) has become a policy priority in recent years for many Latin American public health systems looking to reinforce a healthcare model based on PC. However, despite being a longstanding concern, it has scarcely been analyzed in this region. This paper analyses the level of clinical coordination between PC and SC experienced by doctors and explores influencing factors in public healthcare networks of Argentina, Brazil, Chile, Colombia, Mexico and Uruguay. A cross-sectional study was carried out based on a survey of doctors working in the study networks (348 doctors per country). The COORDENA questionnaire was applied to measure their experiences of clinical management and information coordination, and their related factors. Descriptive analyses were conducted and a multivariate logistic regression model was generated to assess the relationship between general perception of care coordination and associated factors. With some differences between countries, doctors generally reported limited care coordination, mainly in the transfer of information and communication for the follow-up of patients and access to SC for referred patients, especially in the case of PC doctors and, to a lesser degree, inappropriate clinical referrals and disagreement over treatments, in the case of SC doctors. Factors associated with a better general perception of coordination were: being a SC doctor, considering that there is enough time for coordination within consultation hours, job and salary satisfaction, identifying the PC doctor as the coordinator of patient care across levels, knowing the doctors of the other care level and trusting in their clinical skills. These results provide evidence of problems in the implementation of a primary care-based model that require changes in aspects of employment, organization and interaction between doctors, all key factors for coordination. © 2017 The Authors